New insights into the role of histamine in subventricular zone-olfactory bulb neurogenesis - Eiriz, Maria F.; Valero, Jorge; Malva, João O.; Bernardino, Liliana (Frontiers in Neuroscience, 2014)
The subventricular zone (SVZ) contains neural stem cells (NSCs) that generate new neurons throughout life. Many brain diseases stimulate NSCs proliferation, neuronal differentiation and homing of these newborns cells into damaged regions. However, complete cell replacement has never been fully achieved. Hence, the identification of proneurogenic factors crucial for stem cell-based therapies will have an impact in brain repair. Histamine, a neurotransmitter and immune mediator, has been recently described to modulate proliferation and commitment of NSCs. Histamine levels are increased in the brain parenchyma and at the cerebrospinal fluid (CSF) upon inflammation and brain injury, thus being able to modulate neurogenesis. Herein, we add new data showing that in vivo administration of histamine in the lateral ventricles has a potent proneurogenic effect, increasing the production of new neuroblasts in the SVZ that ultimately reach the olfactory bulb (OB). This report emphasizes the multidimensional effects of histamine in the modulation of NSCs dynamics and sheds light into the promising therapeutic role of histamine for brain regenerative medicine.